Comment on “Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study” - Caviglia, Gian Paolo; Fagoonee, Sharmila (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Caviglia GP, Fagoonee S. Comment on “Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study”. Turk J Gastroenterol 2018; 29: 719.